A review on preventive measures and treatment of white spot lesions in patients with fixed orthodontic appliances - Biria, Mina; Jafary, Maral (Journal of Dental School, 2019)
Objective: One complication of fixed orthodontic treatment in patients with poor oral hygiene is development of demineralized enamel lesions compromising esthetics. This study aimed to review preventive measures and treatment of white spot lesions (WSLs) in patients with fixed orthodontic appliances. Review of Literature: In this review study, PubMed and Google Scholar databases were searched for articles published during 1964-2013 using the keywords “white spot lesions”, “demineralization”, “mastic gum”, “casein phosphopeptide amorphous calcium phosphate or CPP-ACP”, “chitosan” and “orthodontics”; 96 articles were evaluated. Conclusion: White spot lesions can be prevented by conventional plaque control and adjunct measures such as the use of fluoride-containing compounds, chlorhexidine (CHX), xylitol gums, chitosan compounds and laser. Low-concentration fluoride, CPP-ACP compounds and laser help remineralize these lesions. If not treated, bleaching, microabrasion and tooth restoration are the final solutions.